Everyday life of pedagogy students suffering from depression in the academic space - Szczupał, Bernadeta; Wiśniewska, Jolanta Izabela (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
Contemporary civilization and cultural changes mean that students experience many psychological, social and physical challenges that may contribute to mental difficulties and disorders. The article presents the results of qualitative research on the opinions of female pedagogy students suffering from depression on the social determinants of their illness, their difficulties studying and the availability of support. Studies have shown that students suffering from depression have a strong need to obtain specialist psychological support at the university.